THE INFLUENCE OF BRAND LOVE, BRAND IDENTITY, AND BRAND IMAGE ON BRAND LOYALTY TO MAKE OVER PRODUCTS - Cindy Fatia Suhelen; Nurainun; Siti Maimunah; Rusydi Abubakar (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2024)
This research aims to analyze the influence of brand love, brand identity, and brand image on brand loyalty in Make Over cosmetic products. This researchuses a quantitative method by collecting data from surveys distributed to Make Over product users, using primary data obtained by distributing questionnaires to 150 respondents selected using the Non Purposive Sampling method. The data analysis method used is the multiple linear regression method with the help of SPSS version 26.0. In testing the validity of the data, researchers used multiple confirmatory factor analysis. The results of this research show that brand love influences brand loyalty in make over products, brand identity influences brand loyalty in make over products and brand image influences brand loyalty in make over products.